One year clinical efficacy and reverse cardiac remodelling in patients with severe mitral regurgitation and reduced ejection fraction after MitraClip© implantation. (August 2013) - Pleger, Sven T.; Schulz‐Schönhagen, Marius; Geis, Nicolas; Mereles, Derliz; Chorianopoulos, Emmanuel; Antaredja, Muliadi; Lewening, Markus; Katus, Hugo A.; Bekeredjian, Raffi
<x xml:space="preserve">Abstract</x> Aims The aim of the present study was to investigate 1 year clinical and functional efficacy of percutaneous mitral valve (MV) repair using MitraClip™ in high‐risk surgical patients with symptomatic severe MV regurgitation (MR) and reduced LVEF. Methods and results Between September 2009 and November 2011, 59 patients with reduced EF and severe MR received endovascular MV repair using MitraClip™. Patients were characterized after 1 and 12 months using echocardiography, 6 min walk test distance, and cardiac biomarkers. The predicted 30‐day surgical perioperative mortality rate was 11.4 ±2.2% using the Society of Thoracic Surgeons' score. Complete 1‐year clinical follow‐up was achieved in 70% of the patients (n = 41; EF 33 ±3%). Percutaneous MV repair resulted in significantly reduced MR and improved NYHA functional class, translating into significantly increased 6 min walk test distance, while high‐sensitive troponin T (P < 0.05) and NT‐proBNP (non‐significant) were reduced. Echocardiography revealed structural reverse remodelling with significantly reduced left atrial volume and LV end‐systolic diameter, as well as significantly increased LVEF. These results were consistent in a subgroup of patients with severely reduced LVEF (EF 23 ±2%; n = 25). Thirty‐day mortality was 2.9%. Conclusion Percutaneous MV repair using MitraClip™ is a safe technique in high‐risk surgical patients, causing significant 1 year reduction of MR which results in structural cardiac reverse remodelling and an increased LVEF. The present data encourage percutaneous MV repair in heart failure patients.